Gothic Fiction Elements in Pedro Almodóvar’s The Skin I Live In (2011) - Jelena Pataki (Anafora, 2016)
The aim of this paper is to explore the elements of Gothic fiction in the critically acclaimed Spanish director Pedro Almodóvar’s 2011 film The Skin I Live In. The film is often viewed as a distinctly modern piece of art in that it dwells on contemporary issues referring to complex ethical and moral dilemmas connected to genetic engineering and the disintegration of an individual’s identity. However, despite the undeniable presence of the said issues, the idea is to show that the film’s structure is in fact solidly built on a much older Gothic fiction matrix featuring many of its well-established, easily discernible motifs and conventions. Starting with the classic Gothic topos – a helpless heroine set in an eerie, claustrophobic architecture, and a grotesque atmosphere evoking a feeling of imminent doom – the paper will consider the film’s portrayal of concepts such as death, doubles, and dreams in order to show that the work of the Spanish director bears many similarities to the canonical Anglophone genre. Inevitably, the analysis will also examine the distinct parallel between Mary Shelley’s seminal Gothic fiction text, Frankenstein, and the contemporary counterparts of its mad scientist and his Creation embodied by Almodóvar’s Dr Robert Ledgard and his Vera.